PENINGKATAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS V DENGAN PEMBELAJARAN KONTEKSTUAL PADA MADRASAH IBTIDAIYAH - ahmad01, ahmad01; Ayu Kurniawati, Kiki Riska; Perwira Negara, Habib Ratu (Jurnal El-Hikam, 2021)
This study aims to determine the improvement of learning achievement, the obstacles experienced by teachers and how to solve problems in improving the mathematics learning achievement of fifth grade students with contextual learning at MI Nurul Yaqin Kelanjur, Montong Sapah Village, Praya Barat Daya District. This type of research is qualitative research, namely research conducted to analyze the problems obtained and then describe them so that clear information can be obtained about what is being studied. The results of this study are Contextual Learning / Contextual Teaching Learning can increase enthusiasm, motivation, understanding and student learning achievement in mathematics subjects, the problems faced during the contextual learning process are many students who bring various objects when asked to bring objects. in accordance with the material to be taught and requires a long time for the learning process. Meanwhile, the teacher's efforts in solving these problems are that the teacher must be creative when the contextual learning process is carried out